Generalized Riemann problem for the one-dimensional Chaplygin gas equations with a friction term. (January 2023) - Singh, Mayank; Arora, Rajan
Abstract: In this paper, we obtain the solution to the generalized Riemann problem (GRP) for the one-dimensional Euler's equation for Chaplygin gas equations with Coulomb-like friction term by using the differential constraint method. The compatibility condition between differential constraints and the basic governing model is derived here. For non-constant and smooth initial data, the solution to the generalized Riemann problem is presented with a complete characterization of the solutions.